Nutrition Considerations in the Pediatric Cardiac Intensive Care Unit Patient. Issue 3 (May 2018) - Justice, Lindsey; Buckley, Jason R.; Floh, Alejandro; Horsley, Megan; Alten, Jeffrey; Anand, Vijay; Schwartz, Steven M.
Adequate caloric intake plays a vital role in the course of illness and the recovery of critically ill patients. Nutritional status and nutrient delivery during critical illness have been linked to clinical outcomes such as mortality, incidence of infection, and length of stay. However, feeding practices with critically ill pediatric patients after cardiac surgery are variable. The Pediatric Cardiac Intensive Care Society sought to provide an expert review on provision of nutrition to pediatric cardiac intensive care patients, including caloric requirements, practical considerations for providing nutrition, safety of enteral nutrition in controversial populations, feeding considerations with chylothorax, and the benefits of feeding beyond nutrition. This article addresses these areas of concern and controversy.